Shifts in composition of avian communities related to temperate-grassland afforestation in southeastern South America - Dias, Rafael A.; Bastazini, Vinicius A. G.; Gonçalves, Maycon S. S.; Bonow, Felipe C.; Müller, Sandra C. (Iheringia. Série zoologia, 2013)
Afforestation of temperate grasslands with fast-growing trees for industrial pulpwood production is spreading in South America. Despite high afforestation rates resulting from governmental policies that stimulate pulpwood production in grasslands of southern Brazil and Uruguay, the impact of this activity on biodiversity remains to be properly assessed. We used an Impact-Reference study design to evaluate how grassland afforestation affects the composition of grassland bird assemblages. We sampled eucalyptus plantations and neighboring natural grasslands in southern Brazil from 2006-2009, and relied on nested sampling and analysis to separate the effects of afforestation from the natural variability of grasslands. We recorded a significant difference in composition between assemblages from grasslands and tree plantations. Species adapted to open, treeless areas tended to be negatively affected in relation to edge or forest birds in eucalyptus plantations. Afforestation is systematically replacing the bird assemblage of hilltop grasslands by a collection of common edge and forest species that occur in nearby riverine and hillside forests. Although most grassland birds negatively affected by tree plantations are common and widespread, observed and predicted afforestation rates in southeastern South America may result in regional population reductions in the near future. O florestamento de campos temperados com árvores de crescimento rápido para a produção industrial de celulose está aumentando na América do Sul. Apesar das elevadas taxas de florestamento resultantes de políticas governamentais que estimulam o plantio de árvores para celulose em campos do sul do Brasil e Uruguai, o impacto dessa atividade sobre a biodiversidade ainda carece de avaliação adequada. Utilizamos um delineamento experimental do tipo impacto-referência para avaliar como o florestamento dos campos afeta a composição da assembleia de aves campestres. Amostramos plantações de eucalipto e campos nativos no sul do Brasil entre 2006-2009 e nos valemos de amostragem e análise aninhada para separar os efeitos do florestamento da variabilidade natural dos campos. Registramos uma diferença significativa na composição entre as assembleias de aves do campo e de plantações de eucalipto. Espécies adaptadas a áreas abertas destituídas de árvores foram afetadas negativamente pelo florestamento, ao passo que aves florestais ou de borda de floresta foram favorecidas pela plantação de eucalipto. O florestamento está sistematicamente substituindo a assembleia de aves de campos de topos de morros por uma coleção de espécies de floresta e de borda comuns em matas ciliares e de encosta. Apesar de a maioria das espécies campestres afetadas negativamente pelas plantações de árvores serem comuns e de ampla distribuição, as taxas de florestamento observadas e previstas no sudeste da América do Sul podem gerar reduções populacionais regionais num futuro próximo.